2019
DOI: 10.1007/5584_2019_401
|View full text |Cite
|
Sign up to set email alerts
|

How Genomics Is Changing What We Know About the Evolution and Genome of Bordetella pertussis

Abstract: The evolution of Bordetella pertussis from a common ancestor similar to Bordetella bronchiseptica has occurred through large-scale gene loss, inactivation and rearrangements, largely driven by the spread of insertion sequence element repeats throughout the genome. B. pertussis is widely considered to be monomorphic, and recent evolution of the B. pertussis genome appears to, at least in part, be driven by vaccine-based selection. Given the recent global resurgence of whooping cough despite the wide-spread use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 95 publications
0
8
0
Order By: Relevance
“…From the 1990s, therefore, aP began to be rolled out globally by the World Health Organisation (WHO) and was incorporated into the primary immunisation schedule of most high-income countries (HICs) [ 7 , 8 ]. Despite high vaccine coverage rates (especially in HICs), however, there has been a resurgence in Bp disease worldwide and it remains a primary cause of vaccine-preventable death [ 9 , 10 ]. Recent models have indicated that there were 24.1 million pertussis cases and 160,700 deaths in children younger than 5 years worldwide in 2014, with the highest burden in sub-Saharan Africa, although these are estimates given the paucity of pertussis epidemiological data to date [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…From the 1990s, therefore, aP began to be rolled out globally by the World Health Organisation (WHO) and was incorporated into the primary immunisation schedule of most high-income countries (HICs) [ 7 , 8 ]. Despite high vaccine coverage rates (especially in HICs), however, there has been a resurgence in Bp disease worldwide and it remains a primary cause of vaccine-preventable death [ 9 , 10 ]. Recent models have indicated that there were 24.1 million pertussis cases and 160,700 deaths in children younger than 5 years worldwide in 2014, with the highest burden in sub-Saharan Africa, although these are estimates given the paucity of pertussis epidemiological data to date [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is strong evidence that vaccine-induced immunity exerts a selective pressure on B. pertussis , leading to antigenic drift and the loss of expression of vaccine antigens [ 3 , 5 , 8 ]. The surveillance of antigen production by B. pertussis isolates aims at detecting the potential emergence and dissemination of B. pertussis strains evolving towards vaccine escape.…”
Section: Discussionmentioning
confidence: 99%
“…PRN-deficient B. pertussis isolates have progressively increased in frequency in countries where aPV are used including France, Italy, Japan and the United States (US) [ 5 ], whereas no or very few PRN-negative isolates have been reported in countries that have continued the use of wPV, such as Iran [ 6 ]. Moreover, the proportion of PRN-negative B. pertussis isolates observed in a given country correlates positively with the time elapsed since the transition from wPV to aPV [ 7 , 8 ]. Finally, a reversion to aPV that do not contain PRN was associated with reversal of the evolutionary trend towards PRN-negative B. pertussis populations, as observed in Japan [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent whole genome sequencing and chromosomal analyses of circulating Bp (cBp) strains changed the prevailing view of Bp as a monomorphic pathogen with small genetic changes and SNPs. Instead, cBp strains represent a dynamic population whose genomes exhibit extensive structural rearrangements including large inversions, duplications, and deletions [3,4]. Nonetheless, comparative genomics alone cannot sufficiently explain pertussis resurgence.…”
Section: Genotypic and Phenotypic Variations Between Vaccine Referencmentioning
confidence: 99%
“…Strain-specific differences in production of three Fim serotypes have also been observed. These results have led to the hypothesis that due to aPV-induced selection pressure, divergence in aPV antigens is observed at higher rates than in factors not included in aPV [3,5]. However, whether these genotypic and phenotypic differences result in the reduction of aPV efficacy remains controversial.…”
Section: Genotypic and Phenotypic Variations Between Vaccine Referencmentioning
confidence: 99%